Drug conciliation as a patient safety criterion in a private hospital in Fortaleza – CE (Research, Society and Development, 2022)
One of the barriers available to avoid errors related to medications and consequently increase the level of safety of hospitalized patients, is medication reconciliation. The present study analyzed, through a drug conciliation service, the impact generated for patient safety through the clinical pharmacy in a private hospital in Fortaleza, Ceará. The results obtained over a period of 12 months were described and consolidated, characterizing the impacts generated by drug reconciliation. The investigation was a cross-sectional, retrospective and documentary study, in which data collected from pharmaceutical visits performed on patients hospitalized in 7 care units and 1 semi-intensive care unit in 2019 were analyzed. The quality of the drug conciliation service, focusing on patient safety. As a result, A total of 3,383 patients were admitted to the hospital's inpatient units, of which 2,700 (79.81%) received a visit from the pharmaceutical conciliation service, in which 461 (17.07%) patients presented medication errors due to omission of medications for continuous use, compared to hospital prescription. We conclude with this data it demonstrates the high prevalence of drugs that are not reintroduced in the pharmacotherapy of hospitalized patients, which may induce clinically important consequences.